Effect of the treatment with Achyrocline satureioides (free and nanocapsules essential oil) and diminazene aceturate on hematological and biochemical parameters in rats infected by Trypanosoma evansi - Do Carmo G.M. (2015)
© 2014 Elsevier Inc.This study aimed to verify the effect of the treatment with A. satureioides essential oil (free and nanoencapsulated forms) and diminazene aceturate on hematological and biochemical variables in rats infected by Trypanosoma evansi. The 56 rats were divided into seven groups with eight rats each. Groups A, C and D were composed by uninfected animals, and groups B, E, F and G were formed by infected rats with T. evansi. Rats from groups A and B were used as negative and positive control, respectively. Rats from the groups C and E were treated with A. satureioides essential oil, and groups D and F were treated with A. satureioides nanoencapsulated essential oil. Groups C, D, E and F received one dose of oil (1.5 mL kg-1) during five consecutive days orally. Group G was treated with diminazene aceturate (D.A.) in therapeutic dose (3.5 mg kg-1) in an only dose. The blood samples were collected on day 5 PI for analyses of hematological (erythrocytes and leukocytes count, hemoglobin concentration, hematocrit, mean corpuscular and mean corpuscular hemoglobin concentration) and biochemical (glucose, triglycerides, cholesterol, alanine aminotransferase (ALT), aspartate aminotransferase (AST), albumin, urea and creatinine) variables. A. satureioides administered was able to maintain low parasitemia, mainly the nanoencapsulated form, on 5 days post infection. On the infected animals with T. evansi treated with A. satureioides essential oil (free and nanocapsules) the number of total leucocytes, lymphocytes and monocytes present was similar to uninfected rats, and different from infected and not-treated animals (leukocytosis). Treatment with A. satureioides in free form elevated levels of ALT and AST, demonstrating liver damage; however, treatment with nanoencapsulated form did not cause elevation of these enzymes. Finally, treatments inhibited the increase in creatinine levels caused by infection for T. evansi. In summary, the nanoencapsulated form showed better activity on the trypanosome; it did not cause liver toxicity and prevented renal damage.